Rosenberg自尊量表的密集性追蹤測量 - 曾明基(Ming-Chi Tseng) (Jiao yu yu xin li yan jiu, 2024)
This study measured the dynamic changes and influencing factors of the Rosenberg Self-Esteem Scale across individuals and time through intensive longitudinal measurement. Participants were 119 senior elementary school students who were repeatedly measured for 100 times on the Rosenberg Self-Esteem Scale. Through the analysis of the cross-classify factor model, it was found that the reliability and validity of self-esteem did not change with time, and showed a stable measurement state across time, but the measurement intercept and factor loading of self-esteem across students have random variation. Through dynamic structural equation model analysis, it can be seen that there is a first-order correlation in students’ self-esteem. Recommendations are made based on the research findings